ATTITUDES OF SECONDARY VOCATIONAL SCHOOL STUDENTS IN SERBIA ON THE USE OF DIGITAL TECHNOLOGIES WHEN CONDUCTING EMERGENCY DISTANCE TEACHING DURING THE COVID-19 PANDEMIC IN THE SUBJECT OF SOCIOLOGY - Nastić, Nevena (Metodička teorija i praksa, 2024)
The method used in this research is an online questionnaire, which was conducted among students of the third and fourth grades of secondary vocational schools in the Republic of Serbia, on a sample of 586 students. The research included the broader context of teaching in secondary vocational schools, respectively students who attended sociology classes during the COVID-19 pandemic, and only one part of it is presented in the paper. In the researched period, the participants of the educational process had to adapt to the new conditions of the COVID-19 pandemic, in which it was ensured that the teaching took place in the safest possible way for all participants, and through the use of modern technologies. Compared to traditional teaching, teachers had to communicate with students through numerous platforms that were available to them free of charge, and as our research on students who attended sociology classes online showed that in 100% of cases they used audio and video recordings, zoom, viber, presentations that teachers sent to them via e-mail and social networks. While to a lesser extent they used Microsot times and significantly less edmondo, moodle and Kahoot. They also used all these online resources to the greatest extent via laptops and mobile phones and to a lesser extent tablets, as well as a few of them via desktop computers. Bearing in mind that the goal of this research was oriented towards investigating the advantages and disadvantages of online or hybrid sociology classes, it is necessary to say that the advantages stand out: that online classes are better and that is why it is easier to learn online, then that the more time they spend at home, and the more free time they have, which indicates a better balance between school and personal obligations. On the other hand, if we take into account that students were given the option not to answer the question if they think that online sociology teaching has no advantages, and we received only 342 answers out of a potential 586 students, we still conclude that a large number of students do not consider online sociology teaching to be took place during the COVID-19 pandemic satisfactorily. Although the online teaching of sociology, which took place in emergency situations, provides a lot of flexibility in teaching, the challenges and shortcomings that accompany it should not be overlooked, and according to the results of our research, there were some. The disadvantages that stand out the most are technical problems and bad internet, lack of motivation, concentration and lack of interest, poor mutual communication. The consequences of identified deficiencies can have a significant impact on learning such as unsatisfactory results and reduced efficiency, but also have long-term consequences for the development of students and their motivation to work in the future.